2017
DOI: 10.1038/s41598-017-12833-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential humoral mediators of remote ischemic preconditioning in patients undergoing surgical coronary revascularization

Abstract: Remote ischemic preconditioning (RIPC) by repeated brief cycles of limb ischemia/reperfusion may reduce myocardial ischemia/reperfusion injury and improve patients‘ prognosis after elective coronary artery bypass graft (CABG) surgery. The signal transducer and activator of transcription (STAT)5 activation in left ventricular myocardium is associated with RIPC´s cardioprotection. Cytokines and growth hormones typically activate STATs and could therefore act as humoral transfer factors of RIPC´s cardioprotection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 109 publications
1
30
0
1
Order By: Relevance
“…We found that RIPC induces the expression of IL-6 at the preconditioned hindlimb muscle and increases plasma IL-6 secretion in vivo ( Figure 4A,B), a finding that aligns with our previous in vitro findings [32]. However, Gedik and colleagues did not detect any significant change in IL-6 levels in arterial plasma sample collected after RIPC from patients undergoing elective CABG [74]. Age, presence of co-morbidity, medications, anesthetic regimen, and extent of preconditioning stimuli may all interfere with the cardioprotective modalities of RIPC [13] and may explain the discrepancy with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…We found that RIPC induces the expression of IL-6 at the preconditioned hindlimb muscle and increases plasma IL-6 secretion in vivo ( Figure 4A,B), a finding that aligns with our previous in vitro findings [32]. However, Gedik and colleagues did not detect any significant change in IL-6 levels in arterial plasma sample collected after RIPC from patients undergoing elective CABG [74]. Age, presence of co-morbidity, medications, anesthetic regimen, and extent of preconditioning stimuli may all interfere with the cardioprotective modalities of RIPC [13] and may explain the discrepancy with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Достаточно подробно, хотя и не до конца, изучен механизм защитного эффекта ишемического прекондиционирования. Короткие эпизоды ишемии приводят к выбросу в системный кровоток таких биологически активных веществ, как аденозин, брадикинин и эндорфины [8,9], увеличивается концентрация оксида азота [10], интерлейкина-1а [11], а также специфической микро-РНК 144 [12]. В результате запускаются процессы антиоксидантной защиты, повышается противовоспалительный потенциал.…”
Section: Discussionunclassified
“…In a randomized subprotocol (amendment: 08-21-2011, also approved by the ethics commission), we used a proof-of principle design to prospectively investigate whether the RIPC maneuver results in a changed EV concentration along with the search for humoral factors transferring a protective RIPC signal [21]. For the present in vitro study, EVs from 10 randomly selected patients (n = 5 RIPC, n = 5 Sham) matched for similar demographics were used.…”
Section: Patient Studymentioning
confidence: 99%